Manifesto for Digital Social Touch in Crisis - Jewitt, Carey; Price, Sara; Steimle, Jürgen; Huisman, Gijs; Golmohammadi, Lili; Pourjafarian, Narges; Frier, William; Howard, Thomas; Ipakchian Askari, Sima; Ornati, Michela; Panëels, Sabrina; Weda, Judith (Frontiers in Computer Science, 2021)
This qualitative exploratory research paper presents a Manifesto for Digital Social Touch in Crisis - a provocative call to action to designers, developers and researchers to rethink and reimagine social touch through a deeper engagement with the social and sensory aspects of touch. This call is motivated by concerns that social touch is in a crisis signaled by a decline in social touch over the past 2 decades, the problematics of inappropriate social touch, and the well documented impact of a lack of social touch on communication, relationships, and well-being and health. These concerns shape how social touch enters the digital realm and raise questions for how and when the complex space of social touch is mediated by technologies, as well the societal implications. The paper situates the manifesto in the key challenges facing haptic designers and developers identified through a series of interdisciplinary collaborative workshops with participants from computer science, design, engineering, HCI and social science from both within industry and academia, and the research literature on haptics. The features and purpose of the manifesto form are described, along with our rationale for its use, and the method of the manifesto development. The starting points, opportunities and challenges, dominant themes and tensions that shaped the manifesto statements are then elaborated on. The paper shows the potential of the manifesto form to bridge between HCI, computer science and engineers, and social scientists on the topic of social touch.